Measurement of the effective B0s → J/ψK0S lifetime - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; Grünberg, Oliver; et al. (Nuclear physics. B, Particle physics, 2013)
This paper reports the first measurement of the effective Bs0→J/ψKS0 lifetime and an updated measurement of its time-integrated branching fraction. Both measurements are performed with a data sample, corresponding to an integrated luminosity of 1.0 fb−1 of pp collisions, recorded by the LHCb experiment in 2011 at a centre-of-mass energy of 7 TeV. The results are: τJ/ψKS0eff=1.75±0.12(stat)±0.07(syst) ps and B(Bs0→J/ψKS0)=(1.97±0.23)×10−5. For the latter measurement, the uncertainty includes both statistical and systematic sources.
Im Titel ist "0" hochgestellt und "s" und "S" tiefgestellt
LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Di Canto, F. Dordei, C. Färber, M. Fontana, E. Gersabeck, O. Grünberg, S. Hansmann-Menzemer, T. Hartmann, A. Jaeger, K. Kreplin, G. Krocker, B. Leverington, C. Linn, J. Marks, M. Meissner, T. Nikodem, D. Popov, M. Schmelling, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, D. Volyanskyy, C. Voß, H. Voss, R. Waldi, S. Wandernoth, D. Wiedner, M. Zavertyaev, A. Zhelezov und weitere 595
Gesehen am 24.03.2021